2019
DOI: 10.1039/c8ta10562f
|View full text |Cite
|
Sign up to set email alerts
|

Trimetallic PdCuIr with long-spined sea-urchin-like morphology for ambient electroreduction of nitrogen to ammonia

Abstract: A one-step method is proposed to synthesize long-spined sea-urchin-like PdCuIr nanostructures for electrocatalytic nitrogen reduction to ammonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…This rate of NH 3 decreases as expected at higher applied potentials due to the competing HER, which is kinetically faster than NRR. [28] Control experiments under open circuit potential in N 2 , and at À0.1 V in Ar confirmed that there is no interference from the applied gas impurity, environment, and the catalyst system itself. These control experiments results are corroborated well with both approaches, as shown in Figure 2 d,e.…”
Section: Methodsmentioning
confidence: 82%
“…This rate of NH 3 decreases as expected at higher applied potentials due to the competing HER, which is kinetically faster than NRR. [28] Control experiments under open circuit potential in N 2 , and at À0.1 V in Ar confirmed that there is no interference from the applied gas impurity, environment, and the catalyst system itself. These control experiments results are corroborated well with both approaches, as shown in Figure 2 d,e.…”
Section: Methodsmentioning
confidence: 82%
“…Similarly, Wang and co-workers fabricated trimetallic compound containing Ir, Pd, Cu (PdCuIr) as an NRR electrocatalyst. [188] It produced NH 3 . [189] The better performance was attributed to lowering of activation of energy and suppression of HER.…”
Section: Ir Compoundsmentioning
confidence: 99%
“…Similarly, Wang and co‐workers fabricated trimetallic compound containing Ir, Pd, Cu (PdCuIr) as an NRR electrocatalyst. [ 188 ] It produced NH 3 at 13.29 µg h −1 mg cat −1 rate with 5.29% efficiency. Though results are not as so high as expected, trimetallic idea would be enough to encourage others take up and extend the work by mixing other metals and optimize the performance.…”
Section: Transition Metals or Elementsmentioning
confidence: 99%
“…Considerable reports have been discussed this problem from both theoretical and experimental aspects. For instance, long‐spine urchin‐like structure of PdCuIr (PdCuIr‐LS) was prepared by a facile one‐pot method [47] . PdCuIr‐LS exhibited excellent catalytic performance for NRR with NH 3 formation rates of 13.43 μg mg cat −1 h −1 and FEs of 5.29% in the neutral medium, due to its hyper‐branched structure and tri‐metallic composition effect.…”
Section: Nrr On Noble Metal (Viii) Catalystsmentioning
confidence: 99%